2012
DOI: 10.1088/1748-9326/7/4/045804
|View full text |Cite
|
Sign up to set email alerts
|

Linking electricity and water models to assess electricity choices at water-relevant scales

Abstract: Hydrology/water management and electricity generation projections have been modeled separately, but there has been little effort in intentionally and explicitly linking the two sides of the water-energy nexus. This paper describes a platform for assessing power plant cooling water withdrawals and consumption under different electricity pathways at geographic and time scales appropriate for both electricity and hydrology/water management. This platform uses estimates of regional electricity generation by the Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…Water impacts were aggregated from the ReEDS model regions to the 18 U.S. Geological Survey Hydrologic Unit Code watershed regions (Seaber et al 1987). Data aggregation techniques follow those described in Macknick et al (2012b) and Sattler et al (2012). ReEDS incorporates the cost, performance, and water-use characteristics of different generation fuel-technology and cooling-system combinations, and it considers water availability as a condition for new power-plant construction.…”
Section: Methodsmentioning
confidence: 99%
“…Water impacts were aggregated from the ReEDS model regions to the 18 U.S. Geological Survey Hydrologic Unit Code watershed regions (Seaber et al 1987). Data aggregation techniques follow those described in Macknick et al (2012b) and Sattler et al (2012). ReEDS incorporates the cost, performance, and water-use characteristics of different generation fuel-technology and cooling-system combinations, and it considers water availability as a condition for new power-plant construction.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Ould-Amrouchea et al (2010) and Campana et al (2013) investigated photovoltaic (PV) water pumping systems and Alawaji et al (1995) analyzed desalination plant size with PV in Saudi Arabia. Similarly, Dubreuil et al (2013) estimated the energy used to process and supply drinking water and Stillwell et al (2011), Sattler et al (2012), van Vliet et al (2013, and Koch and Vögele (2013) estimated the water used to supply energy by coupling hydrologic with energy (e.g., thermal power plant) models.…”
Section: Review Of Water-energy Modeling Approachesmentioning
confidence: 99%
“…This issue provides perhaps the most comprehensive and integrated effort to assess the water implications of electric power generation in the U.S., both at the national level and also with a high enough level of spatial resolution to assess watershed-level impacts. This issue includes the following sets of analyses: (a) a review of water factors from the primary literature [23 ] and comparison of reported and calculated water use [22]; (b) description of a linked energy and water modeling framework (ReEDS and WEAP) [44]; (c) modeling of low carbon electricity futures [37], with assessment of the water impacts of those scenarios at the national and regional level [34 ]; and (d) linking the results of the electricity scenarios with models of regional water systems for the southeastern U.S. [31,43] and southwestern U.S. [32,42].…”
Section: Long-term System-level Trends In Water For Energymentioning
confidence: 99%